Observations on the systematic position of the genus Gaigeria Railliet & Henry, 1910 (subfamily Necatorinae Lane, 1907: family Ancylostomidae Lane, 1907: Nematoda) - Johnson, Sylvester (1965)
On the basis of the form and length of the dorsal lobe of the bursa and the shape of the spicules, as observed in Gaigeria pachyscelis and Bunostomum trigollocephalum, both genera are considered distinct and sepárate, and the former not a synonym of the latter.